Identifying design alternatives for the Windhoek municipality by applying the FAST diagram - Shiimi, Mary (Department of Construction Economics and Management, 2019)
Purpose - Value management has been in use for many decades, yet in Namibia most built environment professionals are vaguely familiar with the concept and are not aware of the benefits of this practice, and that it can add value for money without reducing quality. This research seeks to focus on the value management methodology and more specifically give insight into the use of the Functional Analysis Systems Technique (FAST) diagram in the built environment within a local government context. Design/methodology/approach - To establish how a FAST model can be used as a tool to design roads and introduce alternative materials with a focus on reducing cost for municipal projects. This would address the design methods, design team composition, construction methods and availability of material taking environmental sustainability into consideration. The benefits and cost of value management are reviewed and the importance of value management as an integrated practice of the project management process of the Municipality is explored. A quantitative method is used to determine the applicability of the FAST diagram within the project team and current project environment. A likert Scale questionnaire was used to establish the current use of value management techniques, effectiveness of project implementation process and additional challenges related to availability of material in the Windhoek Municipality. Results – The research delineated project management challenges which reduce project success rate. It also outlines the impact of FAST model and its advantages. This includes improving project cost, monitoring and successful execution of a construction project. The FAST has a positive impact on challenges as established by the research. Project risks are mitigated early during the planning, composition of the project team, efficiency is improved and scope is managed. There is a reduction in time and cost overrun resulting in improved project success. Limitations – Given the exploratory nature of this research, the amount of data is restricted to a single municipality of Namibia.